el-Bidâye ve'n-nihâye - 880-01 İbn Kesîr, Ebü'l-Fidâ, 1301/02-1373. (Beyrut Beyrut Beyrut Beyrut Beyrut)
14 cilt 8 ciltte (1. c. 318 sayfa , 2. c. 334 sayfa ; 3. c. 352 sayfa , 4. c. 378 sayfa ; 5. c. 314 sayfa , 6. c. 366 sayfa ; 7. c. 381 sayfa , 8. c. 357 sayfa ; 9. c. [373] sayfa , 10. c. 375 sayfa ; 11. c. 390 sayfa , 12. c. 389 sayfa ; 13. c. 386 sayfa , 14. c. 349 sayfa ; fihrist 625 sayfa)